Pillar[4]arene[1]thioarenes: Synthesis and Host-Guest Binding Properties - Adisorn Khanthong (2022)
The synthesis and characterization of a novel class of pillar[4]arene[1]thioarenes (P[4]A[1]SMe) are reported. An oxidation-thionation strategy was used to replace a single dialkoxybenzene panel in the parent pillar[5]arene. 1H NMR spectroscopic titration experiments, supported by density functional theory computational studies, revealed that P[4]A[1]SMe show starkly modulated host-guest binding properties for electron-deficient aliphatic guests.